PERSEPSI MAHASISWA CALON GURU TERHADAP POTENSI ROBLOX SEBAGAI RUANG BELAJAR VIRTUAL DALAM PERSPEKTIF UTAUT - Liddya Ganda Asmara; Gema Rullyana; Linda Setiawati; Fikri Dwi Oktaviani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Digital transformation demands innovation in immersive learning spaces through the metaverse, but student teachers' acceptance of platforms like Roblox still needs in-depth exploration. This study aims to describe these perceptions using the Unified Theory of Acceptance and Use of Technology (UTAUT) framework. Using a descriptive quantitative approach, a survey was conducted among 200 Indonesian education students selected through purposive sampling. The research stages included instrument validity and reliability testing, data collection through a Google Form questionnaire, and descriptive statistical analysis using mean and percentage values. The findings indicate that respondents' exposure to Roblox is very high; 96.5% of respondents are familiar with the platform and 70% have used it. Interest in utilizing it in learning is considered positive, reaching 58.5%. The quantitative results of the UTAUT constructs show that all dimensions are in the high category, led by social influence (3.80), followed by performance expectancy (3.74), behavioral intention (3.69), facilitating conditions (3.64), and effort expectancy (3.56). The main conclusion confirms that student teachers have initial readiness and positive acceptance of Roblox as an immersive virtual learning space. Although Roblox is still predominantly viewed as an entertainment gaming platform, its potential as a collaborative learning space is vast, provided it is supported by structured pedagogical design, strengthened digital technology literacy, and adequate institutional policy support to sustainably and comprehensively transform dynamic educational experiences in the future. ABSTRAK Transformasi digital menuntut inovasi ruang belajar imersif melalui metaverse, namun penerimaan mahasiswa calon guru terhadap platform seperti Roblox masih perlu dieksplorasi secara mendalam. Penelitian ini bertujuan mendeskripsikan persepsi tersebut menggunakan kerangka Unified Theory of Acceptance and Use of Technology (UTAUT). Melalui pendekatan kuantitatif deskriptif, survei dilakukan kepada 200 mahasiswa kependidikan di Indonesia yang dipilih secara purposive sampling. Tahapan penelitian mencakup uji validitas serta reliabilitas instrumen, pengumpulan data melalui kuesioner Google Form, serta analisis statistik deskriptif menggunakan nilai mean dan persentase. Temuan menunjukkan paparan responden terhadap Roblox sangat tinggi; 96,5% responden mengenal platform tersebut dan 70% pernah menggunakannya. Minat pemanfaatan dalam pembelajaran tergolong positif mencapai 58,5%. Hasil kuantitatif konstruk UTAUT menunjukkan seluruh dimensi berada pada kategori tinggi, dipimpin oleh social influence (3,80), diikuti performance expectancy (3,74), behavioral intention (3,69), facilitating conditions (3,64), dan effort expectancy (3,56). Simpulan utama menegaskan bahwa mahasiswa calon guru memiliki kesiapan awal dan penerimaan positif terhadap Roblox sebagai virtual learning space imersif. Meskipun Roblox masih dominan dipandang sebagai platform permainan hiburan, potensinya sebagai ruang belajar kolaboratif sangat terbuka lebar, asalkan didukung oleh desain pedagogis terstruktur, penguatan literasi teknologi digital, serta dukungan kebijakan institusional yang memadai untuk mentransformasi pengalaman pendidikan yang dinamis di masa depan secara berkelanjutan tuntas.